Effect of Body Posture on Cardiovascular Performance and Recovery during Cycling Exercise - Albarrati, Ali (Physikalische Medizin, Rehabilitationsmedizin, Kurortmedizin, 2017)
This study aimed to assess the acute effects of posture position (upright vs. semi recumbent) during mild to moderate-intensity cycling exercise and recovery on cardiovascular indices in young healthy adults as there is little information on this subject.
Keywords: cardiovascular indices; cycling; posture; recovery